KESADARAN LITERASI DIGITAL: PELUANG, TANTANGAN DAN KERENTANANNYA BAGI KOMUNITAS LAUT-PULAU (Suatu Pemikiran) - Pieter Agusthinus Riupassa; Anneke Pesik (Pattimura Proceeding, 2022)
Digital literacy has been supported by the development of information technology in Industry 4.0 which has significantly changed and enabled many opportunities for advancement in the community learning dimension. The system connected to the internet network and the availability of information (i.e. science, technology, and art) is a golden opportunity to create the achievements of the marine-isle community, which is always under the stigma of being fallen behind, so that they can get out of the poverty trap into a space of empowerment and mental readiness to enter the era of a new revolution. The approach were used socio-scientific interpretive and narrative method. This article aim is to reflect and capture the existence of the marine-isle community to inspire and motivate young learners to take advantage of easy access to information, and pinned a number of mentality attitudes (soft skills) to achieve success in life. A number of high awareness attitudes in changing the way of thinking and behavior patterns to motivate persons and our society. Thus, at least at the social level, inherent values, hidden internally to develop into young learners with digital characters who are adaptive, proactive, and dynamic. Otherwise, with anxiety, the community will be crushed and shackled by the hustle and bustle of digital advances